Experimental Study on the Shear Strength of Cement-Sand-Gravel Material - Jie Yang; Xin Cai; Qiong Pang; Xing-wen Guo; Ying-li Wu; Jin-lei Zhao (Advances in Materials Science and Engineering)
An experimental study on the shear strength development of cement-sand-gravel (CSG) material was carried out using triaxial compression tests. The effects of the cementing agent content, aggregate content, and gradation on the shear strength of CSG material were analyzed. The shear strength remarkably increased with increasing cementing agent content and aggregate content for a given confining pressure. The increase in shear strength with increasing cementing agent content far exceeded that with increasing aggregate content. However, the stress-strain curves and shear strength changed only slightly when the aggregate gradation for CSG material was adjusted. Based on the test data, a strength criterion for CSG material is proposed as a function of the cementing agent content, aggregate content, and shear strength of the aggregate gradation.